COVID-19 in India: Impacts on Production, Poverty & Food Systems - Pal, Barun Deb; Pradesha, Angga; Thurlow, James (2021)
Barun Deb, Angga Pradesha and James Thurlow International Food Policy Research Institute Last updated: October 9, 2020